Serum level of S100A8/A9 as a biomarker for establishing the diagnosis and severity of community-acquired pneumonia in children - Xie, Si; Wang, Jun; Tuo, Wenbin; Zhuang, Shihao; Cai, Qinzhen; Yao, Cong; Han, Feng; Zhu, Hongmin; Xiang, Yun; Yuan, Chunhui (Frontiers in Cellular and Infection Microbiology, 2023)
Background S100A8/A9, which is a member of S100 proteins, may be involved in the pathophysiology of Community-acquired pneumonia (CAP) that seriously threatens children’s health. However, circulating markers to assess the severity of pneumonia in children are yet to be explored. Therefore, we aimed to investigate the diagnostic performance of serum S100A8/A9 level in determining the severity of CAP in children. Methods In this prospective and observational study, we recruited 195 in-hospital children diagnosed with CAP. In comparison, 63 healthy children (HC) and 58 children with non-infectious pneumonia (pneumonitis) were included as control groups. Demographic and clinical data were collected. Serum S100A8/A9 levels, serum pro-calcitonin concentrations, and blood leucocyte counts were quantified. Results The serum S100A8/A9 levels in patients with CAP was 1.59 ± 1.32 ng/mL, which was approximately five and two times higher than those in healthy controls and those in children with pneumonitis, respectively. Serum S100A8/A9 was elevated parallelly with the clinical pulmonary infection score. The sensitivity, specificity, and Youden’s index of S100A8/A9 ≥1.25 ng/mL for predicting the severity of CAP in children was optimal. The area under the receiver operating characteristic curve of S100A8/A9 was the highest among the indices used to evaluate severity. Conclusions S100A8/A9 may serve as a biomarker for predicting the severity of the condition in children with CAP and establishing treatment grading.